2SPD-023 How much does falsified medicines directive actually costs? Detailed cost evaluation of serialisation in a representative sample of Hungarian hospital pharmacies. (24th March 2020) - Fittler, A; Richter, K; Vajda, P; Bodrogi, Z; Vida, RG; Bella, R; Kovács, S; Zemplényi, A; Botz, L
Abstract : Background and importance: The aim of the falsified medicines directive (FMD 2011/62/EU) is to prevent the entry of illegitimate medicines into the legal supply chain. Despite its proposed benefits, the indepth evaluation of cost implications for hospital pharmacies is still lacking. Aim and objectives: Our study evaluated the current practice of serialisation and the financial impact of the FMD in a representative sample of Hungarian hospitals. Material and methods: Based on literature review and interviews with hospital pharmacy experts, a 41 item questionnaire was developed to evaluate the implementation process leading up to February 2019, and the stabilisation period that followed. Questions regarding institutional data, human resource requirements, infrastructural and IT developments, and authentication procedures were sent out to all (n=96) Hungarian hospital pharmacies in September 2019. Results: A high response rate (n=43, 44, 8%) allowed representative data evaluation of Hungarian hospitals. By the initial launch date of FMD, the average increase in pharmacist workload was 0.92 (±0.98) hours/day, and it was estimated to increase further by 1.13 (±1.65), equalling 0.25 pharmacist full time equivalents (FTE)/institution. Additionally, FMD seemed to increase technician workload significantly compared with pharmacists (p<0.001), as by February, 2.25 (±1.42) hours, and in the long term a further 4.01 (±3, 88) daily working hour increase was reported (equalling approximately 0.75 technician FTE/institution). Average non-human resource (eg, infrastructural, IT, etc) costs related to the implementation of the directive in February 2019 were 1868€/institution with a high variation (±3331€) due to inter-institutional differences but significantly lower costs are expected in the long term in the stabilisation phase (421±785€). FMD has affected the hospital supply chain in numerous ways, as 76.7% of respondents faced drug shortages, 58.1% reported suspected increases in drug costs of serialised medications and 53.5% noticed an increase in packaging size affecting storage capacities. Conclusion and relevance: Our results illustrated that the FMD had notable short and long term impact on hospital pharmacies. Our aim is to adapt this methodology to other EU countries and identify good practices in serialisation at an international level. References and/or acknowledgements: Conflict of interest: Corporate sponsored research or other substantive relationships: The project was supported by the European Union, co-financed by the European Social Fund (EFOP-3.6.1.-16-2016-00004) and by the UNKP-19 new national excellence programme of the Ministry of Human Capacities.